Precast bendable concrete pavement with added self-healing functionality - Tan, Han Siang (2014)
Engineered cementitious composites (ECC) are a group of High Performance Fiber Reinforced Cementitious Composites (HPFRCC) which maintaining tight crack width of about 60μm that satisfied the stingy requirement of intrinsic self-healing mechanism (V. C. Li & Herbert, 2012) From the research of Yang and co-workers in US, good self-healing performance on ECC by using fly ash as replacement material was observed. (Y. Yang, Lepech, Yang, & Li, 2009). Therefore, this report covers effect of local ground granulated blast furnace slag (GGBS) on the self-healing of ECC. Experiment on the recovery of single crack specimens were conducted by the student to verify the self-healing performance of ECC with GGBS under wet and dry cycles. Performance was verified by monitoring of the recovery of stiffness and microscopic observation of crack width before and after the wet and dry cycles. In summary, it was found that the replacement of GGBS content with the cementitious compounds could directly affect the precipitation of white crystals (CaCO3) along the crack surface. Furthermore, the replacement ratio will affect the content of calcium hydroxide (Ca(OH)2) and the leaching of free calcium ions (Ca2+) as a result affecting the precipitation of white crystals. The replacement ratio of 30% with GGBS (GGBS 30) provided the best performance on stiffness recovery followed by GGBS 60 then GGBS 0. GGBS 30 design was found and proved to achieve complete stiffness recovery of transverse resonance frequency for specimens with single crack width less than 86.1μm.